The LC-MS of Grammatophyllum scriptum (Lindl.)Bl. and Cytoxic Activity Test: LC-MS of Grammatophyllum scriptum (Lindl.)Bl. and Cytoxic Activity Test - de Fretes, Christina; Simaremare, Eva; Gunawan, Elsye; Agustini, Verena; Maulana, Yusuf Eka; Fadhilah, Nabila Nur (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Tiger orchid (Grammatophyllum scriptum (Lindl.) Bl.) It is one of the plants that are favored among the community as ornamental plants because of its beautiful flowers. Tiger orchids have secondary metabolite compounds of alkaloids, flavonoids, and tannins that can be used as traditional medicine. However, research on tiger orchids in the field of pharmacology is still very limited. The purpose of this study is to find out the content of chemical compounds contained in the herb extract of tiger orchids (Grammatophyllum scriptum (Lindl.) Bl.) as well as LC₅₀ and concentration of tiger orchid herb extract (Grammatophyllum scriptum (Lindl.) Bl.) It most effectively kills shrimp larvae (Artemia salina Leach.). The sample used was sampled using 96% ethanol. Tiger orchid (Grammatophyllum scriptum (Lindl.) Bl.) pregnant 2′,6′-Dihydroxy-4′-methoxy-dihydrochalcone, apigenin-7-O-α-L-rhamnose(1→4)-6"-O-acetyl-β-D-glucoside, kushenol H, rubrofusarin, 3-hydroxy baicalein and luteolin obtained from the results of the analysis using Liquid Chromatography Mass Spectrometry (LCMS). The results showed that the herb extract of tiger orchid (Grammatophyllum scriptum (Lindl.) Bl.) has cytotoxic activity with an LC₅₀ value of 150.96 ppm.